ENVIRONMENTAL EDUCATION AND HEALTH AND SANITATION BEHAVIOR IN THE CITY OF ZA-KPOTA (REPUBLIC OF BENIN) - YEMADJE, Alda A.S.; AZALOU TINGBE, Fanès V. B.; AZONHE, THIERRY HERVÉ S. NICÉPHORE (My University, 2018)
Environmental issues and their impact on health are one of the major challenges to achieving the goals of sustainable development. The present research aims to contribute to the improvement of the sanitary situation of households in the city of Za-Kpota through environmental education. The methodological approach used consisted in collecting data from 319 households selected on the basis of Schwartz's method (1995). The collected data relate to the state of the environment, the epidemiological profile and the Environmental Education strategies in the study area, and have been processed with the Sphinx software. The results obtained reveal that the proliferation of infectious diseases is linked to both natural factors and the management of people's living conditions (insalubrity, poor sanitation and consumption patterns). However, several environmental education strategies are being implemented in the city to reduce infectious prevalence. These actions for the most part are unprofessional due to the extreme dispersion of the actors and the communication channels used: radio (46%), animation at the health center (17%), television (16%), discussion with friends (11%), about children (5%) and others (5%). Faced with this situation, more operational strategies have been proposed to reduce health risks related to the state of the environment in the population.
Keywords: Environmental Education; environment; insalubrity; diseases; Za-Kpota.